Proporção áurea em modelos biológicos - Vaz, José Murilo Calixto (2014)
Lettuce (Lactuca sativa L.) and onion (Allium cepa L.) plants are of great importance in the diet of Brazilians. They are also widely used in bioassays as the target species, which are important for determining the effect of agents on parts of the body. Knowledge of the morphology of the chromosomes of target species is important. Thus, it is necessary to use methods that allow knowledge of characteristics that relate to the sensitivity and/or resistance of materials within genetically distinct target species. A parameter to be used in karyotype description is the identification of the golden ratio in the arm ratio of chromosome. The golden ratio found in various forms in nature and used in various areas of human knowledge structures confers greater stability and strength. The objective of this study was to evaluate methodologies for the presence of the golden ratio, as well as quantify the karyotypic and morphometric variation in seven genotypes of Lactuca sativa L. and four genotypes of Allium cepa L., and identify and quantify the presence of the golden ratio in the ratio arms of chromosomes of these genotypes. The methodology that establishes the presence of the golden ratio making use of the difference between the largest and smallest segment multiplied by showed better results in the control of Type I error rates and power . There was variation in the karyotype formula of genotypes of the two species used for the study. Identified the presence of the golden ratio in chromosome pairs in all genotypes. There is variation in the number of chromosomes present in the golden ratio between genotypes and species. The species had between one and fourth chromosomes in golden ratio. Cytogenetic findings reported here can be applied as a tool to aid identification of genotypes and Lactuca sativa L. e Allium cepa L. and provide insights for future studies of chromosomal manipulation.